Interactions of yeasts, moulds, and antifungal agents : How to detect resistance - Hall, Gerri S. (Humana Press, 2012)
The incidence of fungal infections increases with the increase in antibiotic usage and increasing immunosuppressed populations. There is no longer only one antifungal agent  and the response of fungi to various agents is not always predictable. The need for standardized antifungal susceptibility testing, and standardized interpretation of results in conjunction with studies that describe clinical outcomes based on those tools is ever important. Interactions of Yeasts, Moulds, and Antifungal Agents: How to Detect Resistance covers the available antifungal agents, how to perform in vitro testing and  how those results should be interpreted for the most common fungal pathogens.